A qualitative decision trail in the hermeneutic analysis evidence from the case study - Selamat, Mohamad Hisyam; Hashim, Azizi @ Hamizi (Canadian Center of Science and Education, 2008)
Qualitative analysis is often reported as an intuitive, personal journey for the researcher. In this case, qualitative research texts are long on discussions of data collection and research experiences but short on analysis. This paper aims to reduce the tension in the qualitative analysis by adopting a decision making trail that is proposed by Clarke(1999). The reason behind this is that a decision trail does provide a clear and agreed analysis processes in qualitative analysis. The case that is utilised to achieve the aims of this paper is that the impact of meta-abilities (cognitive-skills, self-knowledge, emotional resilience and personal drive) in the externalisation and sharing of tacit knowledge. It is found that a decision making trail supports the principles of academic rigour in qualitative research.